2000
DOI: 10.1007/s002109900210
|View full text |Cite
|
Sign up to set email alerts
|

Release of catecholamines in the locus coeruleus of freely moving and anaesthetized normotensive and spontaneously hypertensive rats: effects of cardiovascular changes and tail pinch

Abstract: Noradrenaline turnover has been found to be increased in the locus coeruleus of young spontaneously hypertensive rats (SHR). There is also evidence that the noradrenergic projection from the locus coeruleus to the posterior hypothalamus contributes to the development of genetic hypertension. To investigate whether the release of noradrenaline and dopamine in the locus coeruleus is modified in genetic hypertension, this brain region of adult SHR and normotensive Wistar-Kyoto (WKY) rats was superfused with artif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 24 publications
2
16
0
2
Order By: Relevance
“…In addition, increased release of NA into the PVN was revealed in SHRs (Versteeg et al, 1976;Wijnen et al, 1977;Winternitz et al, 1984;Qually and Westfall, 1993), and this release was especially prominent during the development phase of hypertension in younger animals (Qually and Westfall, 1993). Such enhanced secretion of NA into the PVN in hypertensive rats might be caused by the increased metabolic activity in catecholaminergic brainstem nuclei that is found in these animals in normal (Saavedra et al, 1976;Saavedra, 1979;Koulu et al, 1986;Kawasaki et al, 1991) and even more so in stressful (Kaehler et al, 2000) conditions. It is significant that catecholaminergic brainstem nuclei also seem to be substantially activated in humans with essential hypertension, which is reflected by the significantly elevated overflow of NA and dihydroxyphenylglycol (DHPG) from subcortical region into the minor jugular vein seen in these patients (Ferrier et al, 1993).…”
Section: Discussionmentioning
confidence: 93%
“…In addition, increased release of NA into the PVN was revealed in SHRs (Versteeg et al, 1976;Wijnen et al, 1977;Winternitz et al, 1984;Qually and Westfall, 1993), and this release was especially prominent during the development phase of hypertension in younger animals (Qually and Westfall, 1993). Such enhanced secretion of NA into the PVN in hypertensive rats might be caused by the increased metabolic activity in catecholaminergic brainstem nuclei that is found in these animals in normal (Saavedra et al, 1976;Saavedra, 1979;Koulu et al, 1986;Kawasaki et al, 1991) and even more so in stressful (Kaehler et al, 2000) conditions. It is significant that catecholaminergic brainstem nuclei also seem to be substantially activated in humans with essential hypertension, which is reflected by the significantly elevated overflow of NA and dihydroxyphenylglycol (DHPG) from subcortical region into the minor jugular vein seen in these patients (Ferrier et al, 1993).…”
Section: Discussionmentioning
confidence: 93%
“…Painful stimulation leads to an increase in the expression of Fos, the protein product of the activation of the intermediate early gene c-Fos, a marker of neuronal activity [Bullitt, 1990 (noxious heat and cold, pinch); Pezzone et al, 1993 (electric shock); Palkovits et al, 1995 (subcutaneous formalin injection); Voisin et al, 2005 (electric tooth pulp stimulation); Wang et al, 2009 (colon distension)]. Noxious stimuli evoke an increase in the release of noradrenaline from the LC [Singewald et al, 1999 (air puff, noise stress); Kaehler et al, 2000 (tail pinch); Sajedianfard et al, 2005 (subcutaneous formalin injection)]. A number of neurotransmitters and neuromodulators have been implicated in the modulation of the activation of the LC by noxious stimuli.…”
Section: Processing Of Pain By the Lcmentioning
confidence: 99%
“…Some studies assign them a pressor role [8][9][10] whereas others give them a depressor role [11][12][13] or even suggest no role for that nucleus in such regulation [14,15]. Previous research in our laboratory demonstrated that LC lesions accentuated the hypotensive response to hemorrhage [16].…”
Section: Introductionmentioning
confidence: 98%